Accidental injection of succinylcholine into epidural space as a test dose - Toleska, Marija; Naumovski, Filip; Dimitrovski, Aleksandar (Wolters Kluwer – Medknow, 2020)
Inadvertent injection of nonepidural drugs into the epidural space is a rare situation, which is under-reported, and can lead to serious complications, such as cardiovascular and respiratory complications, paraplegia, or quadriplegia, and can worsen the patients' outcome from surgery. Succinylcholine administered epidurally leads to the appearance of fasciculation and shortness of breath and can prolong neuromuscular blockade. We report a case of accidental administration of 100 mg of succinylcholine via an epidural catheter as a test dose instead of 2 ml 0.5% bupivacaine in a patient planned for major abdominal surgery. After 2 min, the patient complained of shortness of breath; dysarthria; and fasciculation in the trunk, upper limbs, and face. This was managed with induction to general anesthesia (GA). In the postoperative period, no neurological or cardiovascular complications were observed. There is no adequate drug as an antidote of accidentally given nonepidural drugs via an epidural catheter. Succinylcholine given via epidural catheter has been shown to prolong neuromuscular blockade. Proper labeling and storage of syringes are of utmost importance for avoiding these unpleasant situations.
Keywords: accidental administration; epidural catheter; succinylcholine